An Evaluation of Mobility Effect on Tiny Service Discovery Protocol for Wireless Sensor Networks - Salim, Ahmed; El Khatib, Akram (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In mobile sensors environment, nodes change their positions this leads to crucially affects service discovery of wireless sensor networks (WSNs). Therefor the accuracy of most service discovery can be limited to just small area of movement, or demands considerable maintenance efforts in term of neighbor nodes allocation. A large waiting time of wireless sensor applications spent in node discovery, as nodes need to periodically advertise their presence and be awake to discover other nodes for services. The optimization of waiting time, which is generally a hard task in static wireless sensor networks, is even harder in mobile wireless sensor networks, where the neighboring nodes also change over time. In this paper, the effect of node mobility on the performance of Tiny Service Discovery Protocol (TinySDP) in WSNs has been analyze. In order to measure and evaluate the performance of TinySDP in mobile WSNs (MWSN), three major metrics of evaluation has been considered such as, Success ratio, Number of transmitted messages and Average waiting time. Simulation results show that the success ratio and average waiting time of TinySDP in mobile WSNs had decreased and the number of transmitted message increased.